The Digital Economy's Impact on Middle-Class Dynamics in Southeast Asia: A Case Study of Indonesia - Putri, Ratih Astiakurnia; Aziz, Irvan Nurdin; Simon, John Christianto; Aryatama, Septian; Oktapiani, Marliza (GoAcademica Research & Publishing, 2025)
The digital economy has become a major driver of social and economic transformation in Southeast Asia, especially in Indonesia. These changes affect various aspects, including consumption patterns, social interactions, and economic opportunities for the middle class. However, there are still major challenges related to inequality in access to technology that exacerbates social inequality. The purpose of this study is to analyze the impact of the digital economy on the dynamics of the middle class in Indonesia, with a focus on the socio-economic changes that occur due to digitalization. This study uses a qualitative approach by collecting data from previous studies and other relevant sources. The collected data will be analyzed to produce findings explaining the relationship between the digital economy and the middle class in Indonesia. The conclusion of this study shows that the digital economy opens up new opportunities for the middle class, but also creates inequality in access that needs to be addressed. Digital infrastructure and technological literacy are key to reducing this gap. With the right policies, the digital economy can be a tool to drive inclusive growth and social welfare.